Changes of Tumor Markers in Patients with Breast Cancer during Postoperative Adjuvant Chemotherapy. (19th May 2022) - Zhang, Yan; Zhao, Jing; Wang, Yajun; Cai, Wei; Zhang, Xiaoli; Li, Kaifu; Liu, Wenqing; Zhao, Ye; Kang, Hua
Abstract : Objective. Serum tumor marker (STM) elevation can detect metastasis earlier than imaging diagnosis and, although not recommended by guidelines, is still widely used in clinical practice for postoperative follow-up of breast cancer patients. The purpose of this study was to investigate the change rules of CEA and CA153 in patients with HER2-negative breast cancer during postoperative adjuvant chemotherapy and their influencing factors. Materials and Methods. The medical records of patients with HER2-negative early breast cancer who visited Xuanwu Hospital from September 2018 to June 2021 were retrospectively analyzed. Demographic characteristics and baseline data of CEA and CA153 at initial diagnosis were collected. Data of CEA, CA153, biochemistry (including ALT, AST, rGT, triglycerides, cholesterol, and blood glucose) and blood routine (including white blood cells, neutrophils, monocytes, lymphocytes, and platelets) were also collected before chemotherapy, at the end of chemotherapy and more than 3 months after the end of chemotherapy. LY/MONO, NEUT/LY, PLT/LY, and systemic immune inflammation index (SII) were calculated and statistically analyzed using SPSSAU software. Results. A total of 90 patients were enrolled, all of whom were female, with a mean age of 55.11 ± 10.60  y. The value of CEA at initial diagnosis was 2.10 ± 1.11  ng/mL, and high expression was mostly correlated with past history of chronic diseases and tumor lymph node metastasis; the value of CA153 was 11.80 ± 6.60  U/mL, and high expression was correlated with high SII at initial diagnosis. Surgery did not affect the values of serum CEA and CA153. At the end of chemotherapy, CEA and CA153 were 2.68 ± 1.34  ng/mL and 18.51 ± 8.50  U/mL, respectively, which were significantly increased compared with those before chemotherapy, and were linearly correlated with the values before chemotherapy. They decreased (CEA 2.45 ± 1.19  ng/mL, CA153 10.87 ± 5.96  U/mL) again three months after the end of chemotherapy, manifested as "spiking" phenomenon, which was associated with lymph node metastasis at diagnosis, body metabolic disorders, and chronic inflammatory status. Conclusion. CEA and CA153 were increased presenting as "spiking" phenomena in patients with early HER2-negative breast cancer during postoperative adjuvant chemotherapy, and the peak of increase was linearly correlated with the indicators before chemotherapy. Clinical attention should be paid to this change to avoid excessive diagnosis and treatment leading to medical resource consumption.